(untitled) (Revista NUPEART, 2021)
In this research, we investigate the possibilities of teaching cinema in the school, especially in a practical perspective, from a experience of creation by the students. For this, we use the concept of creation pedagogy, a term proposed by Alain Bergala (2008), a scholar of cinema teaching in schools. We applied the theories covered in a course offered to public school students in Recife. It had a practical character, where students had the opportunity to produce their own films. The results obtained in this experience, while showing us interesting and enriching possibilities, alerted us to some problems existing in the implementation of differentiated projects in the school. In spite of this, we concluded that it is possible and necessary to teach cinema at school, above all, based on a pedagogy that emerged in the creation, experimentation, and realization of audiovisual projects by students.